2001
DOI: 10.1182/blood.v97.2.473
|View full text |Cite
|
Sign up to set email alerts
|

The soluble murine type I interferon receptor Ifnar-2 is present in serum, is independently regulated, and has both agonistic and antagonistic properties

Abstract: The ability to modify responses to type I interferons (IFNs) could alter processes such as hematopoiesis and immunity, which involve endogenous IFNs and responses to exogenous IFNs. The data presented here support a significant role for a recently identified soluble isoform of the murine type I IFN receptor, muIfnar2a, as an efficient regulator of IFN responses. The messenger RNA (mRNA) transcript encoding muIfnar-2a is generally more abundant than that encoding the transmembrane isoform, muIfnar-2c. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 38 publications
4
101
0
Order By: Relevance
“…18 Surface expression of full-length IFNR2 is sufficient for binding, but both receptors are required for signal transduction. [19][20][21] Mutational studies suggest that IFNR2 has at least three interferon-a-binding sites, at the A helix (residues 12-15), at the AB loop (residues 26-35) and at the E helix (residues 144-153), 22 whereas the IFNR1-binding site was mapped in the vicinity of K121. 23 The affinity of IFN to IFNR2 (K D B10 nM) is at least 10-fold higher than that to IFNR1 (K D 4100 nM), 24 and it is likely that the rather bulky PEG side chains disturb binding or appropriate positioning of the ligand between its receptors.…”
Section: S Foser Et Al 316 the Pharmacogenomics Journalmentioning
confidence: 99%
“…18 Surface expression of full-length IFNR2 is sufficient for binding, but both receptors are required for signal transduction. [19][20][21] Mutational studies suggest that IFNR2 has at least three interferon-a-binding sites, at the A helix (residues 12-15), at the AB loop (residues 26-35) and at the E helix (residues 144-153), 22 whereas the IFNR1-binding site was mapped in the vicinity of K121. 23 The affinity of IFN to IFNR2 (K D B10 nM) is at least 10-fold higher than that to IFNR1 (K D 4100 nM), 24 and it is likely that the rather bulky PEG side chains disturb binding or appropriate positioning of the ligand between its receptors.…”
Section: S Foser Et Al 316 the Pharmacogenomics Journalmentioning
confidence: 99%
“…Even though these soluble cytokine receptors have been considered as antagonists for transmembrane forms of the receptors, they also perform as carrier proteins to increase the stability of type I IFNs ligands by keeping them from proteolysis and clearance. In this way, they are agonists for modifying ligand activity in a transsignaling pathway (6,9,25,26). On the other hand, it has been demonstrated that the numbers of pDC are decreased in the IFNI-dependent proapoptotic manner in viral hepatitis (9).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Zhao et al (24) showed that the mRNA and plasma levels of IFNAR1 and IFNAR2c were increased in CHB and liver cirrhosis patients compared with healthy controls. Soluble IF-NAR2 is an important regulator of endogenous and systemically administered of type I IFNs (9,25,26). Interferons-α/β are virus-interfering factors that involved in both immunostimulatory and immunosuppressive properties (27).…”
Section: Discussionmentioning
confidence: 99%
“…IFNs are highly conserved across species, highlighting their evolutionary importance in host immune responses against pathogens. Murine IFN−αs have over 70% sequence identity with human IFN−αs [9,10]. However, there is only one IFN−β subtype expressed in both humans and mice [11].…”
Section: Ifn Typesmentioning
confidence: 99%